Determinação de posições precisas de asteróides: ESO, La Silla, fevereiro 1986 - Debhogne, H.; Machado, L.E.; Vaz, Sílio; Netto, E.R. (Anuário do Instituto de Geociências, 1991)
This paper refers to the observation of asteroids at the European Southern Observatory - ESO, La Silla. Chile, made by H. Debehogne (Observatoire Royal de Belgique), during february/march, 1986. The G.P.O. refractor (D= 40 cm; F= 4 m), was used. The plates were reduced at the Observatório do Valongo, UFRJ, using the Ascorecord coordinatograph and the Burroughs 6700 computer of the Núcleo de Computação Eletrônica, of the same University.